TINGKAT PENGETAHUAN MAHASISWA ANGKATAN 2018 FAKULTAS KEDOKTERAN UMSU TENTANG COVID-19 - FADHLA AFIFAH (JURNAL ILMIAH SIMANTEK, 2022)
Coronavirus disease 2019 (COVID-19) is a respiratory infection caused by an emerging coronavirus that was first recognized to appear in Wuhan, China, in December 2019. The increase in cases of the number of COVID-19 is happening quite fast and there is already a spread between countries. Knowledge and understanding regarding COVID-19, the successor of minor cases. There is a need for a valid and credible source of data and information regarding COVID-19. This study aims to determine the level of knowledge of UMSU medical faculty students of 2018 about Covid-19. This research uses a descriptive method. The subjects of this study were students of the 2018 UMSU medical faculty. Data collection using a questionnaire with google form. Data analysis with univariate analysis. The results of the univariate analysis, the level of knowledge of female students in the 2018 batch of UMSU medical faculty was good, namely as many as 98 people (71.53%)